Modeling and Simulation of Permanent Magnet Spherical Motor - سليمان حسن (Latakia University Journal -Engineering Sciences Series, 2021)
This thesis aims to study spherical motors, which can achieve three degrees of freedom motion in one joint, which have wide applications in manufacturing, robotics, automobile and medical industries. First, we present introduction about spherical motor and their applications, and then we present a study about permanent magnet spherical motor in terms of structure and working principle. Second, we present the mathematical model of the spherical motor, where we present kernel function method for modeling electromagnetic torque, as well as the dynamic model of the motor using Euler-Lagrange model. Finally, we present a spherical motor simulation model in the MATLAB/Simulink environment. We used Solid works to study magnetic field distribution and effect of stator and rotor magnetic permeability on the electromagnetic torque. We calculate kernel function for proposed motor and test the working principle. Simulation results showed the efficiency of the proposed model. We proposed a new structure suitable for future practical implementation.